A Hybrid Educational Experience Training Future Health Professionals to Work Together to Improve Patient Outcomes - Iveris Martinez; Colleen Rose-St.Prix (Association of American Medical Colleges, 2013)
Abstract Introduction In alignment with recent strategic planning, this interprofessional workshop was conceived as part of the Florida International University Herbert Wertheim College of Medicine (FIU HWCOM) Green Family Foundation Medicine and Society curriculum. The goal of the workshop is to move beyond silos created through socialization within each discipline and highlight the science that links collaboration to improved quality care and safety, positive patient outcomes, and patient and family-centered care. The workshop was created through collaboration with the participation of seven disciplines: medicine, nursing, social work, occupational therapy, physical therapy, communication disorders, and dietetics. Methods In preparation for the one-half day workshop experience, students completed a series of online modules to increase understanding of the roles and responsibilities of participating disciplines, prior to participating in small-group case-based activities. During the workshop, students observe professionals currently working on teams addressing a case, receive a primer on teamwork, and have the opportunity to work on a case themselves with students from all participating disciplines. Each year we evaluate student perceptions of interprofessional collaboration in health and teamwork before and after the workshop. Results The workshop has been held annually for three academic years. It has grown from 280 students from seven disciplines in 2009 to 367 students from six disciplines in 2011 resulting in a total of 995 student participants to date. Our data indicates that we have increased positive attitudes, knowledge, and skills on interprofessional collaboration on all areas measured for medical students to date. After completing the modules and participating in the workshop, students had a greater sense of their professional limitations (competency RR2) and a self-reported greater ability of communicating their roles to others (competency RR1). For example, when asked: "Shared Learning will help me understand my own professional limitations," the percent change in student responses for pre- to postevaluation increased 10.15% for the agree/strongly agree category (from 84.73% to 94.88%); and, "I am not sure what my professional role will be," the percent change in student responses for pre- to postevaluation increased 18.53% for the agree/strongly agree category (from 72.61% to 91.14%). There was a 15% increase in agreement when asked "Hospital patients who receive team care are better prepared for discharge than other patients" (from 82.2% to 97.47%). Discussion While data indicates that we are making an impact on attitudes towards teamwork, role recognition, and shared ethics of interprofessional collaboration, ultimately the real impact of interprofessional education on student behavior will have to be evaluated in the practice setting postgraduation.